Longer, broader, deeper, and more personal - the renewal of labour history in the Nordic countries - Andersen Nina Trige; Kristjánsdóttir Ragnheiður; Neunsinger Silke; Pesonen Pete; Vilhelmsson Vilhelm; Østhus Hanne (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
This article deals with the recent developments of labour history in and about the Nordic countries. We identify patterns, problems and possibilities in these recent developments in the field - roughly within the last two decades. Our main source of analysis is the research presented and exchanged in the Nordic labour history journals, the Nordic Labour History Network, the labour history associations, the archives and libraries. We relate current trends to developments in European and Global labour history. We claim that the revival and expansion of Nordic labour history must also be understood through its exchange with labour history outside the Nordic sphere and with other disciplines and research fields. The expansion of the field occurred through increased attention and sensitivity to the specificities of various forms of labour, the lived lives of those who work, the places in which work takes place, the various ways in which workers form collective practices and structures, and how they understand themselves in relation to as well as within and outside the parties and institutions that organise and claim to represent workers and labour interests.